Fourier Transform Infrared (FTIR) Spectroscopy Method for Fusarium solani Characterization - Hasanah, Ifa Maulidah; Martosudiro, Mintarto; Aini, Luqman Qurata; Prillianti, Kestrilia Rega; Prabowo, Matheus Randy (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2022)
The detection and identification of microorganisms using spectroscopy techniques promise to be of great value because of their sensitivity, rapidity, low expense, and simplicity. In this study, we used FTIR spectroscopy for the characterization of Fusarium solani. PCR amplification of DNA extracted from these isolates showed the possibility of amplifying PCR products with sizes 559 bp using the ITS1-ITS4 primers. Based on phylogenetic tree analysis, the isolate of F. solani showed a closely relationship to Fusarium solani isolate MN (MH300495.1) with 99.63% similarity. The study is focused on the carbohydrate structure which can be analyzed in the range of 900 to 1200 cm-1 of FTIR wavenumber. The spectra of our samples share similarities with one another, although small differences occur in the absorbance value. The band at 1027 cm-1 is assigned to the C-O stretching of glycogen. Meanwhile, at 1042 cm-1 is interpreted as carbohydrate C-O stretching as well. The band around 1073 cm-1 might arise from both chitin C-C stretching and phosphate stretching of nucleic acids. Other vibrations associated with chitin are also found at 1115 cm-1 and 1151 cm-1 which are assigned to C-O-C symmetric stretching and C-O-C asymmetric stretching, respectively.